Identifying and prioritising midwifery care process metrics and indicators: a Delphi survey and stakeholder consensus process - Declan Devane; Nora Barrett; Anne Gallen; Mary Frances O'Reilly; Margaret Nadin; Gillian Conway; Linda Biesty; Valerie Smith (BMC, 2019)
Abstract Background Measuring care processes is an important component of any effort to improve care quality, however knowing the appropriate metrics to measure is a challenge both in Ireland and other countries. Quality of midwifery care depends on the expert knowledge of the midwife and her/his contribution to women and their babies' safety in the healthcare environment. Therefore midwives need to be able to clearly articulate and measure what it is that they do, the dimensions of their professional practice frequently referred to as midwifery care processes. The objective of this paper is to report on the development and prioritisation of a national suite of Quality Care Metrics (QCM), and their associated indicators, for midwifery care processes in Ireland. Methods The study involved four discrete, yet complimentary, phases; i) a systematic literature review to identify midwifery care process metrics and their associated measurement indicators; ii) a two-round, online Delphi survey of midwives to develop consensus on the set of midwifery care process metrics to be measured; iii) a two-round online Delphi survey of midwives to develop consensus on the indicators that will be used to measure prioritised metrics; and iv) a face-to-face consensus meeting with midwives to review the findings and achieve consensus on the final suite of metrics and indicators. Results Following the consensus meeting, 18 metrics and 93 indicators were prioritised for inclusion in the suite of QCM Midwifery Metrics. These metrics span the pregnancy, birth and postpartum periods. Conclusion The development of this suite of process metrics and indicators for midwifery care provides an opportunity for measuring the safety and quality of midwifery care in Ireland and for adapting internationally. This initial work should be followed by a rigorous evaluation of the impact of the new suite of metrics on midwifery care processes.